2011
DOI: 10.2500/ajra.2011.25.3582
|View full text |Cite
|
Sign up to set email alerts
|

Use of narrow band imaging in evaluation of possible nasopharyngeal carcinoma

Abstract: NBI could be helpful in differentiating benign and malignant neoplasm in the NP region. Using NBI in NP regions had some limitations, including bleeding and mucus coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Computerized tomography and laryngoscopy are the main laryngeal cancer diagnostic and staging modalities. Computerized tomography clearly reveals the anatomic relationship between the tumour and surrounding normal tissues, as well as lymph node metastasis . With NBI laryngoscopy, typical lesions can be acquired according to IPCL morphology, and different laryngeal diseases, including carcinomas, benign tumours, polyps and inflammation, can be identified .…”
Section: Discussionmentioning
confidence: 99%
“…Computerized tomography and laryngoscopy are the main laryngeal cancer diagnostic and staging modalities. Computerized tomography clearly reveals the anatomic relationship between the tumour and surrounding normal tissues, as well as lymph node metastasis . With NBI laryngoscopy, typical lesions can be acquired according to IPCL morphology, and different laryngeal diseases, including carcinomas, benign tumours, polyps and inflammation, can be identified .…”
Section: Discussionmentioning
confidence: 99%
“…Narrow‐band imaging (NBI) is an optical image enhancement technology that enhances the contours and patterns of vessels in the mucosa surface by employing the characteristics of the light spectrum. This newly invented endoscopic technique has been used worldwide for detecting precancerous and neoplastic lesions of the aerodigestive tract, including the oral cavity, nasopharynx, oropharynx, hypopharynx, larynx, esophagus, stomach, and colon 4, 11–28. On review of the literature, studies entirely focusing on oral cavity lesions are few,4, 13, 15 and the various descriptions of NBI images in the upper aerodigestive tract do not seem to conclude a standard.…”
Section: Introductionmentioning
confidence: 99%
“…5 In their patient with nasopharyngeal carcinoma, they described a reversal in the pale-to-dark ratio of the follicles. 7 They too observed that benign lymphoid hyperplasia demonstrated a regular, cobblestone appearance on narrow-band imaging. 5 Ho et al examined narrow-band imaging appearances in nasopharyngeal carcinoma and benign nasopharyngeal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Lin et al reported the successful detection of early nasopharyngeal carcinoma recurrence using narrowband imaging, following the criteria proposed by Kumagai et al 4 A well demarcated, brownish area with brownish spots was found in an area of the nasopharynx otherwise noted to be smooth and symmetrical when viewed with conventional endoscopy. [4][5][6][7][8] Lin et al reported the successful detection of early nasopharyngeal carcinoma recurrence using narrowband imaging, following the criteria proposed by Kumagai et al 4 A well demarcated, brownish area with brownish spots was found in an area of the nasopharynx otherwise noted to be smooth and symmetrical when viewed with conventional endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation